2014
DOI: 10.1563/aaid-joi-d-11-00149
|View full text |Cite
|
Sign up to set email alerts
|

Nonprocessed Adipose Tissue Graft in the Treatment of Peri-Implant Osseous Defects in the Rabbit's Tibiae: A Pilot Study

Abstract: We hypothesized that a new technique using nonprocessed adipose tissue could regenerate bone around dental implants. Eighteen rabbits received 1 implant per tibia surrounded by a surgically created osseous defect. The defects were assigned for treatment into 3 groups: C, AT, and AB. The percentages of bone-to-implant contact were 17.64% ± 16.22% (AB), 3.54% ± 7.08% (AT), and 12.71% ± 10.11% (C) (ρ = 0.25). The use of adipose tissue around surgically created peri-implant osseous defects interferes with bone for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
3
1
Order By: Relevance
“…The adipose tissue seems to impede the bone formation around the implant. Contrary to Godoy Zanicotti et al (26), the results of the present study showed new bone formation in the treatment group (i.e., fragmented adipose tissue graft).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The adipose tissue seems to impede the bone formation around the implant. Contrary to Godoy Zanicotti et al (26), the results of the present study showed new bone formation in the treatment group (i.e., fragmented adipose tissue graft).…”
Section: Discussioncontrasting
confidence: 99%
“…In a pilot study with rabbit’s tibiae, Godoy Zanicotti et al (26) evaluated non-processed adipose tissue graft in the treatment of peri-implant osseous defects. According to the authors, the use of non-processed adipose tissue around surgically created peri-implant osseous defects interfered negatively with the bone formation (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 So, some studies have focused on the adipose tissue graft and whether it is a safe option to achieve bone repair or not. Zanicotti et al 37 evaluated the regenerating capacity of nonprocessed adipose tissue on bone around dental implants and reported that the use of adipose tissue around surgically created peri-implant osseous defects interferes with bone formation. In a study by Merikanto et al, 38 it was shown that rabbits with cranial bone defects can adversely affect osteogenesis when applied only to adipose tissue without isolation of stem cells.…”
Section: Discussionmentioning
confidence: 99%